Seleksi, Karakterisasi, dan Identifikasi Bakteri Penghasil Kitinase yang Diisolasi dari Gunung Bromo Jawa Timur - Soeka, Yati Sudaryati; Sulistiani, Sulistiani (Jurnal Natur Indonesia, 2011)
Selection, characterization and identification of bacteria that can produce chitinase enzyme were isolated fromBromo Mountain, East Java. The 48 isolates were tested for capability to degrade chitine qualitatively, semiquantitatively and quantitatively. The result showed that 2 isolates, B2-4 and NA S4-1 could degrade chitin, withactivities of 4.8. 10-3 and 3.1 . 10-3 U/ml, after 1 and 2 days incubation respectively. By using molecular characterizationmethods, partial sequences of 16S rDNA and the primers 9F & 1510R were identified as Stenotrophomonas sp.